A Role for Protein Kinase Casein Kinase2 α-Subunits in the Arabidopsis Circadian Clock(1)([W])([OA]) - Lu, Sheen X. (American Society of Plant Biologists, 2011)
Circadian rhythms are autoregulatory, endogenous rhythms with a period of approximately 24 h. A wide variety of physiological and molecular processes are regulated by the circadian clock in organisms ranging from bacteria to humans. Phosphorylation of clock proteins plays a critical role in generating proper circadian rhythms. Casein Kinase2 (CK2) is an evolutionarily conserved serine/threonine protein kinase composed of two catalytic α-subunits and two regulatory β-subunits. Although most of the molecular components responsible for circadian function are not conserved between kingdoms, CK2 is a well-conserved clock component modulating the stability and subcellular localization of essential clock proteins. Here, we examined the effects of a cka1a2a3 triple mutant on the Arabidopsis (Arabidopsis thaliana) circadian clock. Loss-of-function mutations in three nuclear-localized CK2α subunits result in period lengthening of various circadian output rhythms and central clock gene expression, demonstrating that the cka1a2a3 triple mutant affects the pace of the circadian clock. Additionally, the cka1a2a3 triple mutant has reduced levels of CK2 kinase activity and CIRCADIAN CLOCK ASSOCIATED1 phosphorylation in vitro. Finally, we found that the photoperiodic flowering response, which is regulated by circadian rhythms, was reduced in the cka1a2a3 triple mutant and that the plants flowered later under long-day conditions. These data demonstrate that CK2α subunits are important components of the Arabidopsis circadian system and their effects on rhythms are in part due to their phosphorylation of CIRCADIAN CLOCK ASSOCIATED1.